2020
DOI: 10.1038/s43246-020-00080-4
|View full text |Cite
|
Sign up to set email alerts
|

Redox-structure dependence of molten iron oxides

Abstract: The atomic structural arrangements of liquid iron oxides affect the thermophysical and thermodynamic properties associated with the steelmaking process and magma flows. Here, the structures of stable and supercooled iron oxide melts have been investigated as a function of oxygen fugacity and temperature, using x-ray diffraction and aerodynamic levitation with laser heating. Total x-ray structure factors and their corresponding pair distribution functions were measured for temperatures ranging from 1973 K in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 42 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…These values were significantly lower than existing data, but are consistent with recent density functional theory calculations [9,21]. Indeed, Shi et al [13] found that in oxygen-rich melts ferric iron is distributed among FeO 4 , FeO 5 and FeO 6 units, whereas under reducing conditions, ferrous iron mostly contains FeO 4 and FeO 5 units.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…These values were significantly lower than existing data, but are consistent with recent density functional theory calculations [9,21]. Indeed, Shi et al [13] found that in oxygen-rich melts ferric iron is distributed among FeO 4 , FeO 5 and FeO 6 units, whereas under reducing conditions, ferrous iron mostly contains FeO 4 and FeO 5 units.…”
Section: Introductionsupporting
confidence: 87%
“…The Fe-O coordination environments of iron-bearing silicate melts and glasses have been extensively studied at a variety of compositions and redox conditions by Raman, Mössbauer and X-ray absorption spectroscopies, and total scattering techniques (X-ray and neutron) [13,15,16,[37][38][39][40][41]. A primary theme throughout previous studies has been the concept of 'networkformers' in tetrahedral positions with bridging oxygens and 'network-modifiers' occupying octahedral sites with more non-bridging oxygens, which can have considerable practical importance for the refining of steel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In this context, iron oxide (Fe 2 O 3 ) nanoparticles have gained substantial attention owing to their biocompatibility, nontoxicity, and magnetic accountability along with their remarkable electro-activity and desirable anti-interference characteristics. 7,8 The high ratio of surface oxygen ion mobility in Fe 2 O 3 generates abundant redox-active sites 9 and triggers heterogeneous redox reactions with higher electrocatalytic activity. 10,11 However, Fe 2 O 3 -based interfaces suffer from inherent shortcomings such as agglomeration, heterogeneous distribution and low charge transfer rate with time due to halffilled d-band orbitals, 12 resulting in poor repeatability, storage difficulty and stability.…”
Section: Introductionmentioning
confidence: 99%